Character Education Values in the Sufism Book of Nuzhah al-Majalis wa Muntakhab an-Nafa’is: Enhancing the Akhlak Tasawuf Course to Foster Moderate Muslim Character at PTKIN - Zubaedi, Zubaedi; Saputra, Adi (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2024)
The purpose of this study was to determine the content of character education values in the Sufism book of Nuzhah al-Majalis wa Muntakhab an-Nafa’is and their effects on reconstructing the morals of Sufism courses for the cultivation of moderate Muslim character values (religious moderation) on the PTKIN campus. The research design uses literature research (library study). Data collection techniques used by researchers include (1) Documentation studies; (2) Interviews; (3) Observation—data analysis using content analysis. The study results reveal that the presence of the department/study program of Sufism can be used as the right solution for modern humans, especially among university students, because Islamic Sufism has all the elements needed by students in the development of their lives. The results of the study found that the values of character education in Sufism moral courses included (1) the nature of repentance, (2) the nature of asceticism, (3) The nature of trustworthiness, (4) The nature of gratitude, (5) The nature of patience; (6) The nature of pleasure; (7) The nature of shidiq; (8) The nature of wara; (9) The nature of reflection; (10) The nature of faqir; (11) The nature of the king; (12) The nature of khauf; (13) The nature of syauq; (14) The nature of confidence; (15) The nature of love; (16) The nature of muraqabah. These character values are based on the Quran and Sunnah in their function to add depth to religious spirituality and become a means of fostering noble character. Tujuan penelitian ini adalah untuk mengetahui isi kandungan nilai-nilai pendidikan karakter dalam kitab tasawuf Nuzhah al-Majalis wa Muntakhab an-Nafa’is dan pengaruhnya sebagai upaya upaya rekontsruksi mata kuliah akhlak tasawuf untuk penanaman nilai-nilai karakter muslim yang moderat (moderasi beragama) di kampus PTKIN. Rancangan penelitian menggunakan penelitian literatur (studi pustaka). Teknik pengumpulan data yang digunakan peneliti meliputi (1) Studi dokumentas; (2) Wawancara; (3) Observasi. Analisis data menggunakan analisis isi. Hasil penelitian mengungkap kehadiran jurusan/program studi ilmu tasawuf dapat dijadikan sebagai solusi yang tepat bagi manusia modern khususnya di kalangan mahasiswa di perguruan tinggi, karena tasawuf Islam memiliki semua unsur yang dibutuhkan oleh mahasiswa dalam perkembangan hidupnya. Hasil penelitian diperoleh temuan nilai-nilai pendidikan karakter pada mata kuliah akhlak tasawuf anatar lain (1) Sifat taubat; (2) Sifat zuhud; (3) Sifat tawakal; (4) Sifat syukur; (5) Sifat sabar; (6) Sifat ridha; (7) Sifat shidiq; (8) Sifat wara; (9) Sifat muhasabah; (10) Sifat faqir; (11) Sifar raja; (12) Sifat khauf; (13) Sifat syauq; (14) Sifat yakin; (15) Sifat cinta; (16) Sifat muraqabah. Nilai-nilai karakter tersebut berdasarkan Alquran dan Sunnah dalam fungsinya menambah dalamnya spiritualitas agama dan menjadi sarana pembinaan akhlak mulia.